Better customer service : simple rules you can apply today - Brewer, Edward C., 1960-; Holmes, Terence L. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"This readable and concise research-based book discusses seven simple rules that will help businesses and individuals improve their customer satisfaction and workplace environments - and make the world a little better and more pleasant. An author team with extensive cross-sector experience provides a foundation that will help improve customer service no matter the type of organization or situation, allowing customization according to industry standards and expectations. Although the basic steps are simple - going all the way back to preschool and kindergarten - they can have a significant positive impact on customer service and on basic human interaction. If an employee follows these simple steps, not only will relationships with customers improve, but so will relationships with co-workers, increasing overall organizational satisfaction. Readers who adopt the principles in this book may also find that their personal relationships improve as well. The primary audience of this work includes any business that desires to improve customer service. However; anyone who works with people will appreciate the conversational tone and specific illustrative examples in this clear and immediately actionable book"--
Come to Class Prepared -- Complete Assignments Neatly and On Time -- Pay Attention -- Show Respect -- Be Courteous and Kind -- Follow Directions -- Always Do Your Best.
OCLC-licensed vendor bibliographic record.
Keywords: Customer services; Customer relations; BUSINESS & ECONOMICS / Customer Service; BUSINESS & ECONOMICS / Organizational Behavior; BUSINESS & ECONOMICS / Skills